Peran Dinamis Generasi Muda Dalam Mendorong Partisipasi Politik di Indonesia - Azizah, Nur; Trisiana, Anita; Yulianto, Agung; Dewi, Aprillia Puspita; Febriyanti, Feni; Andini, Valecia Putri (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
The younger generation plays a crucial role in promoting political participation in Indonesia, especially in the context of advancing democracy. This article discusses the dynamic role of young people in stimulating political voice and action for the future of Indonesia. In recent decades, youth involvement in politics has significantly changed, with an increasing awareness of political rights and the advancement of technology, making information more accessible. Despite challenges such as low trust in the political system and gaps in access to political education, Indonesian youth are becoming more active on various political platforms, both directly and through social media. Using a mixed-methods approach, combining quantitative surveys and qualitative case studies, this research aims to provide insights into how the younger generation can more effectively advocate for their political interests. A total of 69 respondents from various social, educational, and geographical backgrounds participated in the quantitative survey through an online questionnaire. This study also involves qualitative analysis through in-depth interviews and case studies, exploring internal and external factors that influence youth political participation. The findings of this research are expected to encourage more inclusive and sustainable changes in the future.